Teleworking Impact on Wellbeing and Productivity: A Cluster Analysis of the Romanian Graduate Employees - Catană, Ştefan-Alexandru; Toma, Sorin-George; Imbrişcă, Cosmin; Burcea, Marin (Frontiers in Psychology, 2022)
The COVID-19 pandemic has already had an enormous impact on numerous aspects of human society such as health, education, economy, business, or work and created favourable conditions for the expansion of teleworking. The aim of the paper is to identify and analyze five teleworking impact factors that affect the well-being and productivity of Romanian employees. The data were gathered by a quantitative research method through a questionnaire applied to 327 Romanian employees who hold a Bachelor or Master degree. Firstly, they were analyzed and interpreted through a factorial analysis focusing on the five teleworking impact factors. Secondly, the authors carried on cluster analysis, followed by multiple linear regression, using R statistical software. This study shows that there is a plethora of factors that influence the well-being and productivity of employees: individual and societal factors, organizational and work-related factors, technological factors, social factors at home, and social factors at work. Also, the cluster analysis brings to light significant differences between various Romanian employees such as: their gender, income, age, education, and city size.